(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
In this paper, the strategic financing choices of small businesses are examined through the lens of the business life cycle. This article introduces the concept of small business and the approach to small business development. It answers the questions: Why are small businesses important? How to support small business development. This topic includes micro, small and medium-sized enterprises. The article introduces important nuances in our understanding of the role small businesses play in the economy and how small business development requires a clear analysis of the small business sector in any one location